Room-Temperature Luminescence from Ion Beam or Atmospheric Pressure Plasma-Treated SrTiO3 - Song, jng ho; Choi, Jin Moon; Cho, Mann-Ho; Choi, Eun Jip; Kim, Joon Kon; Song, Jong Han (한국진공학회, 2014)
SrTiO3 (STO) single crystal irradiated with a 3-MeV proton beam exhibits blue and green mixed luminescence. However, the same proton beam when used to irradiate STO with a very thin layer of deposited Pt does not show any luminescence. This Pt layer prevents any damage which may otherwise be caused by arcing, which stems from the accumulated surface voltage of tens of kV due to the charge induced by secondary electrons on the surface of the insulator during the ion beam irradiation process. Hence, the luminescence of ion-irradiated STO originates from the modification of the STO surface layer caused by arcing rather than from any direct ion beam irradiation effect. STO treated with atmospheric-pressure plasma, a simple and cost-effective method, also exhibits the same type of blue and green mixed luminescence as STO treated with an ion beam, as the plasma also creates a layer of surface damage due to arcing.